Evaluation of an ultrasound-guided freeze-core biopsy system for canine and feline brain tumors - Adams, Brian S.; Marino, Dominic J.; Loughin, Catherine A.; Marino, Leonard J.; Southard, Teresa; Lesser, Martin L.; Akerman, Meredith; Roynard, Patrick (Frontiers in Veterinary Science, 2024)
Objective To determine if a single brain biopsy utilizing a freeze-core needle harvest system Cassi II under ultrasound guidance provides a diagnostic sample; to evaluate the technique's efficacy in procuring diagnostic samples in comparison with “open” surgical biopsies; and to describe intraoperative complications associated with the technique. Study design Experimental clinical study. Animals Seventeen dogs and four cats with magnetic resonance imaging (MRI) diagnoses of readily surgically accessible intracranial masses. Methods Immediately prior to surgical biopsy (SB), freeze-core biopsy (FCB) sample was obtained from each patient under ultrasound guidance. Results Histopathology results from single FCB samples were found to be in 100% agreement with the SB samples. Freezing artifact was minimal and did not interfere with histopathologic interpretation. There were no intraoperative complications specifically attributable to the use of the FCB system. Conclusion Based on the results of this small experimental study, the FCB system is expected to safely yield diagnostic quality intracranial masses biopsy specimens. Clinical significance This system has the potential of obtaining diagnostic biopsies of more deeply seated brain lesions (i.e., intra-axial tumors considered inaccessible or with large risks/difficulties by standard surgical means) which would provide a definitive diagnosis to guide appropriate therapy.